Contextualizing Indian experiences on COVID-19
1 online resource
Keywords: "This volume captures the social, political, psychological, administrative and policy dimensions of COVID - 19 pandemic in the Indian context. The book is divided into four parts. Part I highlights the social narratives from the underprivileged workers, Asha workers, LGBTIQ+ community and Sanitary workers. It documents their struggles to emerge with mitigation, adaptation and resilience strategies. Part II includes case studies and stories of self-management, mental health of students from rural and urban Maharashtra and of Care givers. It unveils the path of transformation of self to deal with the issues of anxiety and emotional turmoil caused during and due to COVID - 19 pandemic. Part III consists of resilience, philosophical hope and solidarity, which reflects the contribution of seva by Sikh community. It also highlights the contribution of government organizations like Indian Railways, Air India and Employee Provident Fund Organization to provide relief to both people of India and Indians staying abroad to bring back to the country during unprecedented times. Part IV subsumes the responses of various states of India to the COVID -19 pandemic and the implementation of policies by the government of India during those times. Based on empirical research work, this book will be useful for students, teachers, researchers, behavioral scientists, and practitioners of psychology, sociology, human geography, mental health, political science, public health and public policy. This book will also be of interest to policy makers and general public to understand the intricacies involved and essential propositions towards pandemics"--